2017
DOI: 10.1590/1679-78253872
|View full text |Cite
|
Sign up to set email alerts
|

Experiment and Calculation Method of the Dynamic Response of Deep Water Bridge in Earthquake

Abstract: For deep-water long span bridges under earthquakes, the interaction between water and structure will inevitably induce the hydrodynamic force on the structures. Based on the Morison potential fluid theory, a simplified calculation method of hydrodynamic force was proposed. Taken the 3 rd Nanjing Yangtze River Bridge in China as the prototype, the shaking table test for the elevated pile caps was performed. And the results from the experiment and the proposed simplified calculation method were analyzed and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…It was found that the presence of water around the pier reduced the natural frequency of the pier. Similarly, Li et al [6] reported that the vibration periods of bridge piers increased in the presence of water, and the natural frequency of deep-water bridges was low. Under earthquake action, the fluid-structure interaction increased the internal force at the bridge girders and the piers' bottom.…”
Section: Introductionmentioning
confidence: 86%
“…It was found that the presence of water around the pier reduced the natural frequency of the pier. Similarly, Li et al [6] reported that the vibration periods of bridge piers increased in the presence of water, and the natural frequency of deep-water bridges was low. Under earthquake action, the fluid-structure interaction increased the internal force at the bridge girders and the piers' bottom.…”
Section: Introductionmentioning
confidence: 86%
“…To study the elastic dynamic response of bridge piers in water under unidirectional horizontal ground motions, Lai 37 adopted the increased scale factor for the acceleration ( S a = 3) and polymethyl methacrylate (PMMA) with substantially lower elastic modulus ( S E = 1/10) as the model material but kept the scale factor for the density of the structure constant ( S ρ,s = 1) by adding additional mass, to satisfy both the elasticity similitude criterion (i.e., S l = S E / S ρ,s S a ) and the same scale factor of hydrodynamic force ( S H ) with other forces ( S F ). To study the structural behavior of the South Tower of the Nanjing 3rd Yangtze River Bridge, Song et al 17,39,40 and Li et al 41 designed a scaled ( S l = 1/50) model by using steel tubes to mimic the reinforced concrete (RC) bridge piers in the prototype, but the scaled modeling procedure did not follow exactly any existing similitude criteria. Huang 42 designed a scaled ( S l = 1/50) pier model in compliance with the elasticity–gravity similitude criterion (i.e., S l = S E / S ρ,s and S a = 1) by employing rubber with S ρ,s = 1 and S E = 1/50 as the model material.…”
Section: Ust Model Tests On Cylindrical Marine Structuresmentioning
confidence: 99%
“…Then, formula (4) can be rewritten as: is the additional hydrodynamic mass of the underwater structure. Next, formula (5) can be sorted out as: (6) where, M, C and K are the matrices of structural mass, damping and stiffness, respectively. As shown in formula (6), the structural impact of hydrodynamic pressure can be considered as the additional hydrodynamic mass that moves together with the structure.…”
Section: Analysis Of Structural Motions Based On Morison Equationmentioning
confidence: 99%
“…Next, formula (5) can be sorted out as: (6) where, M, C and K are the matrices of structural mass, damping and stiffness, respectively. As shown in formula (6), the structural impact of hydrodynamic pressure can be considered as the additional hydrodynamic mass that moves together with the structure. The coefficient of hydrodynamic inertia force CM depends on the shape of the structure.…”
Section: Analysis Of Structural Motions Based On Morison Equationmentioning
confidence: 99%
See 1 more Smart Citation